Different Strategies of Housing Design - Berrin Çakmaklı, Ayşem (IntechOpen, 2019)
As one of the largest consumers of energy, the housing sector and its unconscious occupants' activities negatively affect the environment. Architects and engineers have a major role in resolving the associated problems while maintaining comfort for occupants. Also very important are environmental education and awareness of appropriate environmental development in designing activity and selecting building materials and products. There are different architectural strategies that are aimed to achieve a low-energy built environment. Determining the needed strategy according to function, economy, and occupant comfort and affordability is the crucial step. This book helps the reader to achieve a sustainable development without destruction of the resources while maintaining a growing universal awareness of protecting the living and non-living environment.